The long arm of parenting: how parenting styles influence crime and the pathways that explain this effect - Simons, Leslie Gordon (Criminology, 2021)
Although several criminological theories suggest that variations in parenting increase the probability of adult crime, most studies limit focus to the association between parenting and adolescent delinquency. Thus, research exploring the association between parenting and adult crime is rare. The present study used path analyses and prospective, longitudinal data from a sample of 318 African American men to examine the effects of eight parenting styles on adult crime. Furthermore, we investigated the extent to which significant parenting effects are mediated by criminogenic schemas, negative emotions, peer affiliations, adult transitions, and involvement with the criminal justice system. Consonant with the study hypotheses, the results indicated that parenting styles with high demandingness, regardless of whether it co-occurred with responsiveness or corporal punishment, reduced the risk of adult crime. On the other hand, parenting styles low on demandingness but high on responsiveness or corporal punishment were associated with a robust increase in risk for adult crime. These parenting effects were mediated, in large measure, by criminogenic schemas and affiliation with adult deviant peers. The findings held after taking into account the effect of adolescent experiences and traits such as delinquency, deviant peer affiliations, community violence, discrimination, negative emotionality, and poor self-control.